Semantic query in a relational database using a local ontology construction - Saeed M. Sedighi; Reza Javidan (South African Journal of Science, 2012)
Semantic Web refers to a Web of linked data in which data can be shared and reused, allowing more uses than the traditional ‘Web of documents’. However, most of the information on the Web is stored in relational databases and such databases cannot be used by the Semantic Web. Relational databases can, however, be used to construct an ontology as the core of the Semantic Web. We propose a new approach which enables Semantic Web applications to access data actually stored in relational databases using a corresponding ontology. In our approach, domain ontologies can be used to formulate relational database queries in order to simplify the data access of the underlying data sources. The method we propose involves two main phases: the construction of a local ontology from a relational database and a semantic query in a relational database using relational database query language (RDQL). In the first phase, we construct a Web ontology language ontology from data in a relational database. In the second phase, we propose a technique to automatically extract the semantics of relational databases and transform this information into a representation that can be processed and understood by a machine. The method proposed is simulated and implemented using Jena and the simulation results show the effectiveness of the proposed approach. Therefore, we propose RDQL as a real alternative to the commonly used structured query language access to relational databases.